Effect of dietary garlic and thyme seed supplementation on the production performance, carcass yield and gut microbial population of broiler chickens - Khin Khin Lay, Phyo Htet Htet Kyaw, Kyaw San Win; Moe, Kyaw Kyaw; Khin Hnin Swe, Aye Aye Maw (Journal of Scientific Agriculture, 2017)
A total of 200 Cobb 500 male broilers were randomly allocated to 4 treatments consisting of 5 replications with 10 chicks each in order to evaluate the effect of dietary garlic and thyme seed supplementation on the production performance, carcass yield and gut microbial population. Treatments were control diet (T1), control diet with 1% thyme seed powder (T2), control diet with 1% garlic powder (T3) and control diet with 0.5% thyme seed and 0.5% garlic powder (T4). Feed intake, body weight, weight gain, feed conversion ratio (FCR), carcass yield was not significantly (p>0.05) improved by dietary treatments compared to control. Escherichia coli (E. coli) count in the gut of broilers did not show significant difference among dietary treatments. However, Lactobacilli count in the gut of broilers significantly (p<0.05) increased in T2 compared to that of T1. Lactobacilli count in the gut of broilers received T1, T3 and T4 did not differ significantly (p>0.05) with each other. It was concluded that thyme seed was reliable as feed additive in the broiler diet and could provide positive advantages to the colonization and proliferation of Lactobacilli.